Low cost smart breaker panel for load disaggregation. (2018) - Persad, Dale; Singh, Arvind; Rocke, Sean; Ramlal, Craig
The electricity industry is in the middle of a shift from operating as a transparent service to one reliant on everyday customer engagement. Understanding consumer behaviour is becoming even more central to the future planning of operations. Load disaggregation, the process of identifying device usage from aggregated load profiles has, therefore, become an important field of study. This paper details a prototype low cost breaker level metre developed as an intermediary between metre level monitoring, which yields the cheapest but most aggregated load profile to plug level monitoring which is the most expensive but requires no disaggregation. The system developed provides real time access to apparent power consumption via a web application. The solution is economical, flexible and easily expandable. The prototype exhibited a low power consumption of less than 1 watt, and is capable of monitoring up to 15 circuits.